2022
DOI: 10.1177/08830738221100327
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Migraine Phenotype Post Traumatic Headache (MPTH) to Guide Overall Recovery From Traumatic Brain Injury

Abstract: Objective: The primary aim of this study is to develop an easy way to identify migraine phenotype posttraumatic headache (MPTH) in children with traumatic brain injury, to treat headache in traumatic brain injury effectively, and to promote faster recovery from traumatic brain injury symptoms overall. Methods: We evaluated youth aged 7-20 years in a pediatric neurology traumatic brain injury (TBI) clinic, assigning a migraine phenotype for post-traumatic headache (MPTH) at the initial visit with the 3-item ID … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Kamins et al found that posttraumatic migraine was associated with prolonged time to recovery compared with no migraine and no headache in children recruited from specialty concussion clinics within 8 weeks of injury. Similarly, Klein et al identified PTH migraine phenotype using the 3-item ID Migraine Screener in children presenting to a hospital brain injury program up to 1 year after concussion. Children with migraine phenotype took longer to recover than those with nonmigraine phenotype; the study did not include children with orthopedic injury or no PTH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kamins et al found that posttraumatic migraine was associated with prolonged time to recovery compared with no migraine and no headache in children recruited from specialty concussion clinics within 8 weeks of injury. Similarly, Klein et al identified PTH migraine phenotype using the 3-item ID Migraine Screener in children presenting to a hospital brain injury program up to 1 year after concussion. Children with migraine phenotype took longer to recover than those with nonmigraine phenotype; the study did not include children with orthopedic injury or no PTH.…”
Section: Discussionmentioning
confidence: 99%
“…3 Emerging research suggests that PTH with migraine features is associated with persisting symptoms after concussion; however, previous studies are limited by small sample sizes, samples consisting only of athletes or recruited from specialty clinics beyond 1 month after injury, and lack of an orthopedic injury (OI) comparison group. [8][9][10] Moreover, little is known about whether the postacute PTH phenotype is independently associated with prolonged recovery after controlling for known risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yerry et al conducted a retrospective study of onabotulinum toxin A to treat PCS [ 81 ] and showed that the patients receiving the toxin manifested significant reduction in headache frequency, intensity, and medication usage. The study also found improvements in cognitive function and quality-of-life measures.…”
Section: Treatmentmentioning
confidence: 99%
“…Although significant strides have been made in treating TBI, and there have been significant improvements in clinical outcomes, the mortality rate among critically-ill patients remains high ( Hägglund, Olivecrona & Koskinen, 2022 ). Inflammation is observed to be significantly related to the prognosis of TBI patients ( Klein et al, 2022 ). Macrophage migration inhibitory factor (MIF), a proinflammatory factor, plays a vital role in stimulating macrophage adhesion and phagocytosis, cytokine production, and inhibiting macrophage migration.…”
Section: Introductionmentioning
confidence: 99%